2014
DOI: 10.1007/s11999-014-3670-2
|View full text |Cite
|
Sign up to set email alerts
|

Is Preoperative Radiation Therapy as Effective as Postoperative Radiation Therapy for Heterotopic Ossification Prevention in Acetabular Fractures?

Abstract: Background Prophylactic approaches to prevent heterotopic ossification after acetabular fracture surgery have included indomethacin and/or single-dose external beam radiation therapy administered after surgery. Although preoperative radiation has been used for heterotopic ossification prophylaxis in the THA population, to our knowledge, no studies have compared preoperative and postoperative radiation therapy in the acetabular fracture population. Questions/purposes We determined whether heterotopic ossificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…In a similar study, when looking at extensile approaches only, Bosse et al [4] found a decrease in the risk of severe HO with the use of radiotherapy. In these two and another study comparing preoperative with postoperative radiotherapy, Brooker Classes III and IV were considered severe [2,4,23]. When comparing radiotherapy with indomethacin, the findings are been less clear.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study, when looking at extensile approaches only, Bosse et al [4] found a decrease in the risk of severe HO with the use of radiotherapy. In these two and another study comparing preoperative with postoperative radiotherapy, Brooker Classes III and IV were considered severe [2,4,23]. When comparing radiotherapy with indomethacin, the findings are been less clear.…”
Section: Discussionmentioning
confidence: 99%
“…From the morphostructural point of view, we witnessed the sedimentation of calcium salts in nodular or laminar formations, sometimes aggregated in small or large masses, in the context of connective fascial-fat, and periarticular, muscular, and subcutaneous tissues [1][2][3]. In the literature, there are no validated therapeutic algorithms or treatment guidelines clearly defined, which is why there is a heavy reliance on personalized choice for some cases [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Treatments such as indomethacin (25 mg 3 times a day), radiation therapy (700cGy) and shock waves, decrease the incidence of this complication by 10% [9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations